Evaluation of blood evacuation efficiency using 99m Tc-RBC imaging: a comparative study of exsanguination tourniquet rings and Esmarch bandages - Liu, Ninghu; Sun, Binbin; Xu, Jianjie; Xu, Jianqiao; Zhao, Keqi; Xu, Shaonan; Su, Xinhui; Zhou, Weifeng (Nuclear medicine communications, 2024)
The objective of this study is to compare the effectiveness of the Esmarch bandage and exsanguination tourniquet rings (ETRs) in blood evacuation procedures using a controlled intra-subject design involving healthy volunteers. A total of 20 healthy adult volunteers (12 males, 8 females) were recruited from the community. Participants underwent blood evacuation procedures on both legs, using the Esmarch bandage on one leg and the ETR on the other. The order of the procedures was randomized. Blood evacuation time, overall blood evacuation rate, and calf blood evacuation rate were measured using 99m Tc-labeled red blood cell imaging. Paired t -tests were conducted to compare the effectiveness of the two methods. The ETRs demonstrated a significantly faster blood evacuation time compared to the Esmarch bandage (mean difference = -41.72 s, P  < 0.0001). The overall blood evacuation rate was slightly higher for the ETRs (mean difference = 1.717%), though not statistically significant ( P  = 0.3680). The calf blood evacuation rate was significantly higher for the ETRs (mean difference = 6.86%, P  = 0.0225). No significant discomfort or adverse reactions were reported by any participants. ETRs are more efficient in terms of blood evacuation time and calf blood evacuation rate compared to the Esmarch bandage, without causing significant discomfort or adverse reactions. These findings suggest that ETRs could be a preferable option in clinical settings for blood evacuation procedures.